Dual‐Layer Spectral–Computed Tomography Enhances the Separability of Calcium‐Based Implant Material from Bone: An Ex Vivo Quantitative Imaging Study. (20th October 2022) - Peña, Jaime A.; Shaul, Jonathan L.; Müller, Michael; Damm, Timo; Barkmann, Reinhard; Kurz, Bodo; Campbell, Graeme M.; Freitag‐Wolf, Sandra; Glüer, Claus‐C.
ABSTRACT: Local treatment of bone loss with an injection of a resorbable, calcium‐based implant material to replace bone has a long history of clinical use. The in vivo discrimination of changes in bone versus implant is challenging with standard computed tomography (CT). However, spectral‐CT techniques enable the separation between tissues of similar densities but different chemical compositions. Dual‐layer spectral‐CT imaging and postprocessing analysis methods were applied to investigate the separability of AGN1 (a triphasic calcium‐based implant) and bone after AGN1 injection in n = 10 male cadaveric femurs ex vivo. Using the area under the curve (AUC) from receiver‐operating characteristic (ROC) analyses, the separability of AGN1 from bone was assessed for AGN1 (postoperatively) versus compact and versus femoral neck cancellous bone (both preoperatively). CT techniques included conventional Hounsfield (HU) and density‐equivalent units (BMD, mg hydroxyapatite [HA]/cm 3 ) and spectral‐CT measures of effective atomic number (Zeff) and electron density (ED). The samples had a wide range of femoral neck BMD (55.66 to 241.71 mg HA/cm 3 ). At the injection site average BMD, HU, Zeff, and ED increased from 69.5 mg HA/cm 3, 109 HU, 104.38 EDW, and 8.30 Zeff in the preoperative to 1233 mg HA/cm 3, 1741 HU, 181.27 EDW, and 13.55 Zeff in the postoperative CT scan, respectively. For compact bone at the femoral shaft the preoperative values were 1124.15 mg HA/cm 3, 1648 HU, 177 EDW, and 13.06 Zeff and were maintained postoperatively. Zeff showed substantially sharper distributions and significantly greater separability compared to ED, BMD, and HU (all p < 0.002, for both regions) with average AUCs for BMD, HU, ED, and Zeff of 0.670, 0.640, 0.645, and 0.753 for AGN1 versus compact and 0.996, 0.995, 0.994, and 0.998 for AGN1 versus femoral neck cancellous sites, respectively. Spectral‐CT permits better discrimination of calcium‐based implants like AGN1 from bone ex vivo. Our results warrant application of spectral‐CT in patients undergoing procedures with similar implants. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).